Optimizing surfactin yield in Bacillus velezensis BN to enhance biocontrol efficacy and rhizosphere colonization - Liu, Tongshu; Zheng, Yanli; Wang, Litao; Wang, Xu; Wang, Haiyan; Tian, Yongqiang (Frontiers in Microbiology, 2025)
IntroductionSurfactins, a class of lipopeptide biosurfactants secreted by plant growth-promoting rhizobacteria (PGPR), have garnered significant attention due to their dual functionality in promoting plant growth and controlling plant diseases. Their potential as biopesticides is underscored by their unique physicochemical properties and biological activities. However, the practical application of surfactin is currently limited by its low yield in natural strains.MethodsThis study aimed to optimize the culture conditions for Bacillus velezensis BN, a strain with exceptional biocontrol properties, to enhance its surfactin yield. Critical factors, including nitrogen sources and amino acid supplementation, were systematically investigated to determine their impact on surfactin production.ResultsThe study revealed that nitrogen sources and amino acid supplementation were pivotal factors influencing surfactin yield. Compared to the baseline, these factors resulted in a remarkable 5.94-fold increase in surfactin production. Furthermore, a positive correlation was established between surfactin yield and biocontrol efficacy. Enhanced surfactin yield was associated with improved antifungal activity, biofilm formation, and rhizosphere colonization capacity of B. velezensis BN on potato plantlets.DiscussionThese findings provide novel insights into the practical application of surfactin and establish a scientific foundation for the development of innovative and eco-friendly antifungal agents suitable for agricultural use. The results demonstrate that optimizing culture conditions can significantly enhance surfactin yield and biocontrol efficacy, thereby highlighting the potential for sustainable agricultural practices.